2014
DOI: 10.1111/ajo.12201
|View full text |Cite
|
Sign up to set email alerts
|

Health knowledge and iodine intake in pregnancy

Abstract: Despite NHMRC guidelines for iodine supplementation during pregnancy, many women were not taking a sufficient iodine supplement. Pregnant women may be inclined to take an iodine supplement if they had greater knowledge of their increased iodine needs during pregnancy. Medical practitioners are best placed to provide this information to pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
6
29
0
Order By: Relevance
“…Previous studies in New Zealand, the United Kingdom, and Australia have also found that pregnant and lactating women have little knowledge about iodine [20,23,25]. In line with these studies, participants had difficulties identifying the most important dietary iodine sources.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous studies in New Zealand, the United Kingdom, and Australia have also found that pregnant and lactating women have little knowledge about iodine [20,23,25]. In line with these studies, participants had difficulties identifying the most important dietary iodine sources.…”
Section: Discussionmentioning
confidence: 59%
“…In these studies, women had difficulties identifying important dietary sources of iodine as well as adverse health outcomes related to iodine deficiency. For instance, only half of the participants in cross-sectional studies among pregnant women in Australia correctly identified seafood as a good source of iodine and more than half of the participants could not identify any adverse health problem related to iodine deficiency [20,25]. Women’s age and educational level may influence their knowledge about iodine [23].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no published studies have assessed adherence to the PFS recommendation in a national sample of Australian women or the adherence to the more recent NHMRC recommendation regarding IS. There is only one Australian study, of 200 women in Victoria, that has examined adherence to the NHMRC's IS recommendation during pregnancy, 13 with other studies in NSW assessing use of iodine‐containing supplements during pregnancy but not adherence to the recommendation 14–16 . National data is also lacking with regards to pregnant women's knowledge of supplement recommendations and associations between knowledge and adherence.…”
mentioning
confidence: 99%
“…This means that up to 40% of women were still not taking recommended iodine supplements, which the authors suggested might be due to women not being informed about the need for supplementation by their antenatal care providers, despite there being written advice on supplements provided in public health facilities across NSW. More recent studies have confirmed these poor rates of supplementation, as well as finding that only 18.5% of pregnant women believed they needed a supplement [44] and only 26% of family doctors reported discussing iodine supplementation with their pregnant patients [45]. For this reason, we strongly recommend further education of antenatal clinicians regarding the importance of iodine supplementation.…”
Section: Mackerras Et Al Evaluated Iodine Status In Aboriginal Austrmentioning
confidence: 85%